2019
DOI: 10.31234/osf.io/mn2je
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contributions of Nonverbal Cues to the Accurate Judgment of Personality Traits

Abstract: In this chapter, we summarize research on nonverbal expressions of behavior (nonverbal cues) and how they contribute to the accuracy of personality judgments. First, we present a conceptual overview of relevant nonverbal cues in the domains of facial expressions, body language, paralanguage, and appearance as well as approaches to assess these cues on different levels of aggregation. We then summarize research on the validity of nonverbal cues (what kind of nonverbal cues are good indicators of personality?) a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Participants may have relied on invalid speech-related cues (e.g., confident speech; Breil et al, 2021) for judgments in the verbal and/or social-emotional domains. Similarly, social-emotional components or other, more general characteristics of the interaction could have contributed to all of these estimates.…”
Section: Accuracy Of Self- Informant- and Stranger-estimates Of Abilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants may have relied on invalid speech-related cues (e.g., confident speech; Breil et al, 2021) for judgments in the verbal and/or social-emotional domains. Similarly, social-emotional components or other, more general characteristics of the interaction could have contributed to all of these estimates.…”
Section: Accuracy Of Self- Informant- and Stranger-estimates Of Abilitiesmentioning
confidence: 99%
“…Compared to scripted videos, spontaneous real-life interactions involve a plethora of cues, out of which some may be valid indicators of abilities but others may impede accurate judgments. A recent meta-analysis reported that, out of all the cues people base their video-based stranger-estimates of intelligence on, only few were also valid and most of those were speechrelated (e.g., ease of understanding; Breil et al, 2021). It would be interesting whether similar findings would emerge in real-life interactions and when considering other abilities like creativity and emotional competence.…”
Section: Limits Of Generalizability and Future Directionsmentioning
confidence: 99%
“…Of pertinence to the present research and the majority of existing studies in the spontaneous trait inferences domain is the focus on nonverbal cues (Ambady & Rosenthal, 1992). Research attention on nonverbal cues such as gestures and facial expressions has remained high for the last few decades (Breil et al, 2021;Murphy & Hall, 2021). This is likely because compared to verbal cues, nonverbal cues are known to be more difficult to suppress, control, and monitor, and hence an individual's traits and internal states are believed to "leak" more through nonverbal channels and be relied on more by observers when making interpersonal judgments (DePaulo, 1992; but see Biel et al, 2013, andHickman et al, 2021, for discussions on the relative importance of verbal cues in the inferences of some traits).…”
Section: Impression Formation From Nonverbal Cuesmentioning
confidence: 96%
“…In many parts of the world, even face-to-face interactions now suffer from incomplete visual information as a result of the COVID pandemic and health practices associated with the "new normal" (e.g., mask wearing). In addition, a recent review (Breil et al, 2021) suggested that despite the underwhelming focus on nonvisual cues in personality trait inferences, paralanguage cues such as loudness and voice expressiveness are actually the most accurate cues to rely on when inferring personality. As such, in the present research, we examined response timing-a nonvisual and nonverbal yet ever-present paralanguage social cue (Archer & Akert, 1977).…”
Section: Impression Formation From Nonverbal Cuesmentioning
confidence: 99%
See 1 more Smart Citation